Managing Customer Issues through a Support Channel Network - Mwegerano, Andi Mawazo (fi=Turun yliopisto|en=University of Turku|, 2014)
The importance of after-sales service or service in general can be seen and experienced by customers every day with industrial as well as other non-industrial services or products. This dissertation, drawing on theory and experience, focuses on practical engineering implications, specifically the management of customer issues in the after-sales phase in the mobile phone arena. The main objective of this doctoral dissertation is to investigate customer after-sales issue management, specifically regarding mobile phones. The case studies focus on issue resolution time and the issue of corrective actions. This dissertation consists of a main body and four peer-reviewed journal articles and one manuscript currently under review by a peer-reviewed journal. The main body of this dissertation examines the elements of customer satisfaction, loyalty, and retention with respect to corrective actions to address customer issues and issue resolution time through literature and empirical studies. The five independent works are case studies supporting the thesis research questions. This study examines four questions: 1) What are the factors affecting corrective actions for customers? 2) How can customer issue resolution time be controlled? 3) What are the factors affecting processes in the service chain? and 4) How can communication be measured in a service chain? In this work, both quantitative and qualitative analysis methods are used. The main body of the thesis reviews the literature regarding the elements that bridge the five case studies. The case studies of the articles and surveys lean more toward the methodology of critical positivism and then apply the interpretive approach in interpreting the results. The case study articles employ various statistical methods to analyze and to interpret the empirical and survey data. The statistical methods were used to create a model that is useful for significantly optimizing issue resolution time. Moreover, it was found that samples for verifying issues provided by the customer neither improve the perceived quality of corrective actions nor the perceived quality of issue resolution time. The term “service” in this work is limited to the technical services that are provided by product manufacturers and after-sales authorized service vendors. On the basis of this research work, it has been observed that corrective actions and issue resolution time are associated with customer satisfaction and hence, according to induction theory, to customer loyalty and retention. This thesis utilizes knowledge of marketing and customer relationships to contribute to the existing body of knowledge concerning information and communication technology for after-sales service recovery of mobile terminals. The established models in the thesis contribute to the existing knowledge of the after-sales process of dealing with customer issues in the field of mobile phones. The findings suggest that process managers could focus more on communication and training provided to the staff as new technology evolves rapidly. The study also suggest the managers formulate strategies for how customers can be kept informed on a regular basis of the status of issues that have been escalated for corrective action. The findings also lay the foundation for the comprehensive objective to control the entire product development process, starting with conceptualization. This implies that robust design should be applied to the new products so that problems affecting customer service quality are not repeated. The objective will be achieved when the entire service chain from product development to the final user can be modeled and this model can be used to support the organization at all levels.

Tämän tohtorinväitöskirjan päätavoitteena on tutkia huoltopalvelua käyttävien asiakkaiden ongelmien hallintaa. Tuotteita hankkineet asiakkaat huomaavat usein kuinka tärkeä asia on hyvin toimiva huolto. Väitöskirjan lähteinä ovat tieteellinen kirjallisuus, tilastomatematiikan teoria ja väittelijän kokemus. Pääpaino on erityisesti matkapuhelinalan myynninjälkeisen vaiheen asiakkaiden ongelmatilanteiden hallinnassa. Väitöskirja koostuu yhteenvedosta ja neljästä vertaisarvioidusta lehtiartikkelista, sekä yhdestä arvioitavaksi annetusta käsikirjoituksesta. Väitöskirjan yhteenvedossa tarkastellaan asiakastyytyväisyyden tärkeimpiä osia, kuten ostouskollisuutta ja asiakkaiden säilyttämistä suhteessa asiakkaiden ongelmien ratkaisemiseen ja siihen tarvittuun aikaan. Tutkimusmenetelminä käytetään kirjallisuustutkimusta ja empiirisiä tutkimuksia. Viisi erillistä tutkimustyötä antavat vastauksen esitettyihin neljään tutkimuskysymykseen: 1) Mitkä tekijät vaikuttavat korjaaviin toimenpiteisiin? 2) Kuinka asiakkaan ongelman ratkaisuaikaa voidaan hallita? 3) Mitkä tekijät vaikuttavat huoltoketjun prosesseihin? 4) Kuinka viestintää voidaan mitata huoltoketjun sisällä? Työssä käytetään sekä määrällisiä (kvantitatiivisia) että laadullisia (kvalitatiivisia) analyysimenetelmiä. Väitöskirjan yhteenvedossa tutkitaan kirjallisuutta niiden elementtien osalta, jotka yhdistävät viisi tapaustutkimusta. Artikkelien tapaustutkimukset nojaavat enimmäkseen kriittisen positivismin metodologiaan ja soveltavat tulkitsevaa lähestymistapaa tulosten tarkastelussa. Artikkelijulkaisuissa käytetään erilaisia tilastomatemaattisia menetelmiä empiiristen tutkimustulosten analysointiin ja tulkitsemiseen. Havaitaan, että mallintamalla huoltoprosessi tilastomatemaattisin menetelmin voidaan ongelmien ratkaisuaikaa optimoida merkittävästi. Tässä työssä termi "huolto" rajoittuu valmistajan tuottamaan sekä valtuutettujen huoltoliikkeiden tarjoamaan tekniseen huoltoon. Tämän tutkimustyön perusteella on huomattu, että korjaustoimenpiteet ja ratkaisuaika liittyvät asiakastyytyväisyyteen ja täten induktioteorian mukaisesti ostouskollisuuteen ja asiakkaiden säilyttämiseen. Työssä hyödynnetään tietämystä markki noinnista ja asiakassuhteista lisäten nykyistä tieto- ja viestintäteknologian tutkimustietoa matkapuhelinten huoltoketjussa. Tutkimus auttaa myös kehittämään menetelmiä, joita käytetään asiakkaiden ongelmatilanteiden hallinnan analysointiin huoltoketjussa. Työn tulokset osoittavat, että johtamistapoihin pitäisi tehdä useita muutoksia. Huoltoprosessien johtajien pitäisi parantaa viestintää huoltoketjun sisällä sekä lisätä henkilöstön koulutusta, koska uusi teknologia kehittyy nopeasti. Työn tulokset antavat myös pohjan sille tavoitteelle, että koko tuotekehitystä ohjattaisiin järjestelmäsuunnittelusta alkaen siten, että uusien tuotteiden kohdalla samoja asiakaslaatuun vaikuttavia ongelmia ei toisteta. Tavoitteeseen päästään, kun koko huoltoketju loppukäyttäjästä tuotekehitykseen pystytään mallintamaan ja käyttämään mallinnusta apuna huolto-organisaation kaikilla tasoilla. Yritysten pitäisi myös kehittää strategioita, joiden avulla asiakkaille voidaan tiedottaa säännöllisesti huollon tai tehtyjen korjaavien toimenpiteiden edistymisestä.